Public Service Announcements for Health Insurance in Nepal: Perspectives from Health Belief Model - Acharya, Devraj; Devkota, Bhimsen; Bhattarai, Radha (Nepalese Journal of Insurance and Social Security, 2020)
Public Service Announcement (PSA) is an advertisement to inform the people sponsored by the public company or the governmental agencies. There were several PSAs implemented to inform the people about health insurance (HI). Data from the Health Insurance Board showed low enrolment with high dropout in health insurance programme (HIP). It was found that the PSAs could not attract the people. Therefore, we assessed the PSAs used for the HIP and amomg them, three Radio/FM jingles, eight TV spots, hoarding board, newspapers, and brochure were evaluated using the Health Belief Model (HBM). We found the almost all PSAs have not covered the constructs of HBM. Most of the PSAs have included primarily perceived benefits and perceived susceptibility but missed to include perceived severity, perceived threats, and self-efficacy. Only benefits focused message could not attract the people. Therefore, we recommend that all PSAs need to have all the features of HBM in the PSA messages while notifying and informing the people.